Photocatalytic degradation of polycyclic aromatic hydrocarbon benzo[a]pyrene by iron oxides and identification of degradation products. (November 2015) - Gupta, Himanshu; Gupta, Bina
Graphical abstract: Highlights: Photocatalytic activity of iron oxides for degradation of benzo[a]pyrene studied. Effect of soil pH, radiation wavelength and oxalic acid on photodegradation studied. Degradation metabolites at different time intervals in soils of various pH studied. Degradation pathways for benzo[a]pyrene under diverse conditions proposed. Provides metabolite data bank which will help to access the toxicity status. Abstract: Photocatalytic decay profiles of polycyclic aromatic hydrocarbon (PAH) benzo[a]pyrene (B[a]P) have been investigated on various synthesized iron oxides and on soil surfaces under a set of diverse conditions. Samples were analysed using the developed HPLC procedure. Results of the present study demonstrate fastest photodisintegration of B[a]P on goethite followed by haematite, magnetite, akaganeite and maghemite, respectively. The effect of soil pH, irradiation wavelength and iron oxide and oxalic acid dose on the degradation of B[a]P was evaluated. The studies revealed enhancement in photodegradation in the presence of oxalic acid due to the occurrence of fenton like reaction. The results showed faster B[a]P degradation under short wavelength UV radiation. Rate constants in acidic, neutral and alkaline soils under optimum dissipation conditions were 1.11 × 10 −2, 7.69 × 10 −3 and 9.97 × 10 −3 h −1, respectively. The study indicates that iron oxides along with oxalic acid are effective photocatalyst for the remediation of benzo[a]pyrene contaminated soil surfaces. The degradation products of B[a]P in the soils of different pH in presence of goethite were identified and degradation pathways proposed. Peaks due to toxic metabolites such as diones, diols and epoxides disappear after 120 h in all the three soils.